2021
DOI: 10.4093/dmj.2020.0272
|View full text |Cite
|
Sign up to set email alerts
|

Lobeglitazone: A Novel Thiazolidinedione for the Management of Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is characterized by insulin resistance and β-cell dysfunction. Among available oral antidiabetic agents, only the thiazolidinediones (TZDs) primarily target insulin resistance. TZDs improve insulin sensitivity by activating peroxisome proliferator-activated receptor γ. Rosiglitazone and pioglitazone have been used widely for T2DM treatment due to their potent glycemic efficacy and low risk of hypoglycemia. However, their use has decreased because of side effects and safety issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…2 A previous retrospective study revealed that the combination of lobeglitazone and DPP4 inhibitor might be more potent than other lobeglitazone-combined regimens. 12 In this respect, our study might be an option when considering adding one more drug in common combination.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…2 A previous retrospective study revealed that the combination of lobeglitazone and DPP4 inhibitor might be more potent than other lobeglitazone-combined regimens. 12 In this respect, our study might be an option when considering adding one more drug in common combination.…”
Section: Discussionmentioning
confidence: 96%
“…Technically, thiazolidinediones (TZDs) are the only insulin sensitizers among various antidiabetic agents. They activate peroxisome proliferator‐activated receptor gamma and simultaneously improve insulin resistance in adipose cells, upregulate glucose uptake and utilization by the muscles, and reduce hepatic glucose production 9‐12 . Considering the pathophysiology of T2DM, which includes insulin resistance and beta‐cell dysfunction, the frequency of TZD usage will probably increase 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contributes to the enhanced binding affinity of lobeglitazone for PPARγ; docking analysis suggests that the binding affinity of lobeglitazone is 12 times higher than those of rosiglitazone and pioglitazone Diabetes Metab J 2022 Forthcoming. Posted online 2022 https://e-dmj.org [34,38]. TZDs represent peripheral insulin sensitizers [1], but lobeglitazone showed beneficial effects on pancreatic β-cell survival and function in an animal study [2].…”
Section: Discussionmentioning
confidence: 99%
“…Lobeglitazone (LOBE) is a potential peroxisome-proliferator-activated receptor α/γ (PPARα/γ) agonist and a newly developed synthetic thiazolidinedione (TZD) class drug for restoration of insulin sensitivity in type 2 diabetes patients [14]. Although primary function of TZDs is anti-diabetic, TZDs are also reported to possess anti-inflammatory effects [15].…”
Section: Introductionmentioning
confidence: 99%